2010
DOI: 10.1590/s0102-86502010000400007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of peritoneal adhesions formation and tissue response to polypropylene - poli (2-hydroxyethyl methacrylate)-(polyHEMA) implant on rats' abdominal wall

Abstract: Purpose: To verify if the composit poli (2-hydroxyethyl methacrylate)-PolyHEMA/polypropylene mesh implanted in the female rat's abdominal wall could be suitable for the prevention of peritoneal adhesions, and for the evaluation of the tecidual response produced by this biomaterial. Methods: Polypropylene meshes (Group PP, n=20) and polypropylene meshes coated with a layer of poli (2-hydroxyethyl methacrylate)-PolyHEMA (Group PH, n=20) were implanted on the abdominal wall of Wistar female rats. Ten animals from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Currently, three major approaches are taken to prevent or reduce post-surgical adhesion: minimizing surgical trauma, anti-fibrotic drugs, and the use of barriers [15]. A variety of materials, such as barrier membranes [16], gels [17] and degradable biocompatible polymers [18], have been applied to reduce adhesion formation by maintaining separation between serosal surfaces [19]. However, these materials are not widely used, due to problems associated with clinical application as well as other limiting factors [20].…”
Section: Resultsmentioning
confidence: 99%
“…Currently, three major approaches are taken to prevent or reduce post-surgical adhesion: minimizing surgical trauma, anti-fibrotic drugs, and the use of barriers [15]. A variety of materials, such as barrier membranes [16], gels [17] and degradable biocompatible polymers [18], have been applied to reduce adhesion formation by maintaining separation between serosal surfaces [19]. However, these materials are not widely used, due to problems associated with clinical application as well as other limiting factors [20].…”
Section: Resultsmentioning
confidence: 99%
“…Among the literatures, there are some related literatures on PP, PE and FE [12-16]. In these published data, there are some inflammatory reactions appeared attached sites [12-16]. Therefore, the knowledge of regional tissue responses to biomaterials is useful for diagnoses of pathological conditions in clinical sites.…”
Section: Discussionmentioning
confidence: 99%
“…Paulo et al . 22 , in a study involving rats and polypropylene mesh implants versus polypropylene with poly-2-hydroxyethyl methacrylate (polyHEMA) hydrogel for abdominal wall defect correction, concluded that the composite mesh of polypropylene alone determined the appearance of adhesions throughout the surface of the mesh. In contrast, the mesh of polypropylene with hydrogel presented low numbers of adhesions with intra-abdominal viscera.…”
Section: Discussionmentioning
confidence: 99%